THE INFUENCE OF LEADERSHIP STYLE, ORGANIZATIONAL CULTURE, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. MITRA AGRO SEMBADA - Reniati; Arbian Eka Putra; Darman Saputra; Feriyadi (JAMBE: Jurnal Akuntansi Manajemen Bisnis dan Ekonomi, 2025)
This study is motivated by the achievement of employee  performance that has not been maximized, which is caused by factors  that influence employees in an effort to achieve performance. This study  aims to determine and analyze the Leadership Style, Organizational Culture, and Work Motivation on Employee Performance at PT Mitra Agro Sembada. This research is a quantitative descriptive analysis research. The number of respondents in this study were 131 people, which were determined using saturated sampling techniques. The analysis model used is multiple linear regression analysis models. The results showed that leadership style, organizational culture, and work motivation partially had a positive and significant effect on employee performance at PT Mitra Agro Sembada. Simultaneous test results show that Leadership Style, Organizational Culture and Work Motivation together have a positive and significant effect on Employee Performance at PT. Mitra Agro Sembada.